PENGEMBANGAN LEMBAR KERJA SISWA UNTUK POKOK BAHASAN ASAM BASA BERBASIS BAHAN ALAM MENGGUNAKAN BUAH PUCUK MERAH (Syzygium campanulatum korth) - Sri Haryati; Susilawati '; Jumaida ' (Jurnal Pendidikan Kimia Universitas Riau, 2016)
The study has been conducted to natural produce based Student- Worksheet (SW) using red fruit buds for acid-base topic. This study is classified as the developmental research. The produced worksheet has been validated through 3 assessments criteria : format, content, and technical. The average score is 3.30 which is considered appropiate to use. From the limited try out at SMA Tribakti and SMA Taruna Pekanbaru, the average gained score is 3.21 which is include as appropiate. From the teachers assessment, the average score is 3.55. That is categorized in to appropiate. The produced worksheet is considered appropiate to be used for the lab work for the acid-base topic.Keyword : Student-worksheet, natural produce, and red fruit buds, acid-base